Selecting Instruments to Measure Quality of Life after Acute Coronary Syndrome: A Literature Review - Khoiriyati, Azizah; Kusnanto; Kurniawati, Ninuk Dian (International Journal of Psychosocial Rehabilitation, 2020)
Quality of life (QoL) is an important aspect to describe the quality of patient care. The use of valid and reliable instruments is a major concern for measuring the quality of life in post-acute coronary syndrome patients. The purpose of the paper was to select existing tools to measure the quality of life after acute coronary syndrome. A review was performed of literature published from 2000-2019, with the following keywords: acute coronary syndrome, quality of life, and psychometric properties or validity. Scopus, MEDLINE, CINAHL, Science Direct, and Proquest were the primary databases utilized for the search of the literature. The criteria to consider when selecting the existing instrument were a match to objective, psychometric evidence, validity, and reliability. The full texts of 10 articles were found for the evaluation and psychometric after acute coronary syndrome. We identified these assessment tools with different psychometric reported two to eight domains of QoL. The number of items contained in the questionnaires ranges from 6 to 74, and all the tools are self-administered. Most of the tools had not reported complete and desirable psychometric properties. Heart quality of life (HeartQoL) is an appropriate instrument to measure the quality of life after acute coronary syndrome patients. Developing a tool for different societies with varied cultural and social characteristics is suggested because socio-cultural factors can influence the quality of life.